Potensi interaksi obat pada pasien skizofrenia di Rumah Sakit Jiwa Mutiara Sukma tahun 2020 - Virnia Wanda Utami; Mudrikah Darajati; Candra Eka Puspitasari (Sasambo Journal of Pharmacy, 2022)
Schizophrenia is a chronic mental disorder characterized by distortions in thinking and behavior. Schizophrenic patients receive antipsychotic therapy (main) and non-antipsychotic (supportive) for a long time. Prescription drugs are given either single or in combination, that can possible for drug interactions. This study objective to determine the potential drug-drug interactions in schizophrenic patients. The design of this study was cross-sectional with purposive sampling technique. The data used is secondary data from the medical records of inpatient schizophrenia patients at the Mutiara Sukma Mental Hospital NTB in 2020 with a retrospective method. The sample data obtained were 109 medical records. The results showed that there were 82,2% of drug interaction cases, namely the combination of risperodone and lorazepam. The number of major interaction cases is 24,2%, moderate is 72,1% and minor is 3,6%. The high incidence of drug interactions in schizophrenic patients requires closely monitored.